2018
DOI: 10.2174/1574892812666171027102627
|View full text |Cite
|
Sign up to set email alerts
|

NLRP3 Inflammasome Activation Inhibitors in Inflammation-Associated Cancer Immunotherapy: An Update on the Recent Patents

Abstract: The vigorous effort to discover and develop agents to specifically inhibit NLRP3 inflammasome activation, may pave the way to therapeutic intervention targeting inflammasome-regulated pathways that are involved in the pathogenesis of various forms of cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 0 publications
1
14
0
Order By: Relevance
“…Clearly, NLRP3 inflammasome activation performed a dual role in cancers . Reports indicated that activated NLRP3 inflammasome contributed to the matastasis of breast cancer and the progression of late stage of melanoma, but it acted as a negative regulator in human hepatocellular carcinoma and colorectal cancer . In our present study, NLRP3 inflammasome activation was demonstrated to play an important role in promoting inflammation‐related lung cancer in vitro, this result was supported by previous studies that NLRP3 inflammasome was upregulated in lung adenocarcinoma and small cell lung cancer in vivo .…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Clearly, NLRP3 inflammasome activation performed a dual role in cancers . Reports indicated that activated NLRP3 inflammasome contributed to the matastasis of breast cancer and the progression of late stage of melanoma, but it acted as a negative regulator in human hepatocellular carcinoma and colorectal cancer . In our present study, NLRP3 inflammasome activation was demonstrated to play an important role in promoting inflammation‐related lung cancer in vitro, this result was supported by previous studies that NLRP3 inflammasome was upregulated in lung adenocarcinoma and small cell lung cancer in vivo .…”
Section: Discussionsupporting
confidence: 89%
“…Together, these data confirmed that NLRP3 inflammasome activation could be enhanced in the cells upon LPS + CTPE exposure than that in the cells exposed to CTPE alone, indicating that NLRP3 inflammasome‐mediated IL‐1β signal was involved in the development of inflammation‐related lung cancer. Clearly, NLRP3 inflammasome activation performed a dual role in cancers . Reports indicated that activated NLRP3 inflammasome contributed to the matastasis of breast cancer and the progression of late stage of melanoma, but it acted as a negative regulator in human hepatocellular carcinoma and colorectal cancer .…”
Section: Discussionmentioning
confidence: 99%
“…72 NLRP3 inflammasome polymorphisms are also associated with the development of certain cancers, including breast cancer, melanoma, and hepatocellular carcinoma (HCC), 73 and NLRP3 inflammasome inhibitors have been patented for potential cancer therapeutic applications. 74 The NLRP3 inflammasome is a multi-subunit cytosolic protein complexes that assembles upon exposure of its pattern recognition receptor, NLRP3, to a broad range of damage-associated molecular patterns or responses induced by them, including extracellular adenosine triphosphate (ATP), crystalline complexes and protein aggregates, mitochondrial dysfunction and lysosomal damage. 75 Assembly of the NLRP3 inflammasome complex forms a scaffold that induces the activation of procapase-1 to catalyze the maturation of IL-1β and IL-18, which promote recruitment of immune cells and enhance the activity of natural killer (NK) and T-cells, to stimulate a localized proinflammatory environment.…”
Section: Inflammationmentioning
confidence: 99%
“…However, recent work suggests that increased NLR Family Pyrin Domain Containing 3 (NLRP3) inflammasome activity, which plays a key role in innate immunity, can regulate EV secretion, with several reports demonstrating direct associations between NLRP3 inflammasome activation and enhanced exosome release rates and changes in exosome cargo compositions . NLRP3 inflammasome polymorphisms are also associated with the development of certain cancers, including breast cancer, melanoma, and hepatocellular carcinoma (HCC), and NLRP3 inflammasome inhibitors have been patented for potential cancer therapeutic applications …”
Section: Introductionmentioning
confidence: 99%
“…Genetic polymorphisms involved with the NLRP3 inflammasome were linked to various diseases, such as rheumatoid arthritis, ankylosing spondylitis, melanoma, liver cancer, lung cancer, and ovarian cancer [79]. Meanwhile, a truncating polymorphism (rs2043211) can produce a nonfunctional CARD8 and induce an amplification of the inflammatory process, or even evolve into cancer [4].…”
Section: Introductionmentioning
confidence: 99%